Reformed Thought on Freedom The Concept of Free Choice in Early Modern Reformed Theology - Asselt, Willem J. van (Willem Jan van); Bac, J. Martin; Velde, Roelf T. te (Grand Rapids Baker Academic, 2010)
This book makes a major contribution to historical scholarship on the problem of free choice and to contemporary debates over determinism and divine foreknowledge of future events. It fills a significant gap in Reformed knowledge by presenting sources i
Keywords: Liberty -- Religious aspects -- Christianity -- History of doctrines. Reformed Church -- Doctrines. Willensfreiheit -- Evangelische Theologie -- Geschichte Neuzeit. Evangelische Theologie -- Willensfreiheit -- Geschichte Neuzeit